The risk of carriage of Salmonella spp. and Listeria monocytogenes in food animals in dynamic populations. Issue 4 (24th June 2016) - Stipetic, Korana; Chang, Yu‐Chen; Peters, Kenlyn; Salem, Ahmed; Doiphode, Sanjay H.; McDonough, Patrick L.; Chang, Yung Fu; Sultan, Ali; Mohammed, Hussni O.
Abstract: Salmonella spp. and Listeria monocytogenes are foodborne pathogens of global importance. We assessed their risks and associated factors in a highly dynamic population of animals. Animal and environmental samples were collected from dairy cattle, sheep, camel and chickens at either the farms or the abattoirs. The pathogens were detected using a combination of bacterial enrichment culture and real‐time polymerase chain reaction (PCR). Data on putative risk factors were collect and analysed for their significance of association with these pathogens. Salmonella spp. were detected at higher proportions in sheep faeces and sheep carcasses in comparison to cattle faeces (odds ratio = 2.4 and 2.2, respectively). This pathogen was less common in milk or carcasses samples from cattle or chickens. Sheep and camel carcass samples were highly contaminated with Salmonella spp. Faecal samples from cattle had the most diverse serovars of Salmonella enterica including S. Newport, S. Haifa, S. Kedougou, S. Kentucky, S. Mbandaka and S. Goettingen. Exotic serovars in sheep included S. Eastbourne, S. Chester and S. Kottnus. Serovars that were shed in camel faeces included S. Newport, S. Bovismorbificans and S. Infantis. In all sampled populations, detection of Salmonella spp. was more likely during warmer months than cold months. Listeria monocytogenes was not common in the targeted populations and was detected at a rate of 2.4%, mainly from sheep carcasses. The study highlights the role of food animals as reservoirs of pathogens across boundaries since all feed are imported in that population from different parts of the world. Abstract : Salmonella spp. and Listeria monocytogenes are foodborne pathogens of global importance. We assessed their risks and associated factors in a highly dynamic population of animals. Animals and environmental samples were collected from dairy cattle, sheep, camel, and chickens either at the farms or abattoirs. Salmonella spp. were detected at higher proportions in sheep and camel feces in comparison to cattle. Serovars that were shed in camel feces included S. Newport, S. Bovismorbificans, S. Infantanis, and S. Roughor.